Cinnamon, a promising prospect towards Alzheimer's disease. (April 2018) - Momtaz, Saeideh; Hassani, Shokoufeh; Khan, Fazlullah; Ziaee, Mojtaba; Abdollahi, Mohammad
Graphical abstract: Abstract: Over the last decades, an exponential increase of efforts concerning the treatment of Alzheimer's disease (AD) has been practiced. Phytochemicals preparations have a millenary background to combat various pathological conditions. Various cinnamon species and their biologically active ingredients have renewed the interest towards the treatment of patients with mild-to-moderate AD through the inhibition of tau protein aggregation and prevention of the formation and accumulation of amyloid-β peptides into the neurotoxic oligomeric inclusions, both of which are considered to be the AD trademarks. In this review, we presented comprehensive data on the interactions of a number of cinnamon polyphenols (PPs) with oxidative stress and pro-inflammatory signaling pathways in the brain. In addition, we discussed the potential association between AD and diabetes mellitus (DM), vis-à-vis the effluence of cinnamon PPs. Further, an upcoming prospect of AD epigenetic pathophysiological conditions and cinnamon has been sighted. Data was retrieved from the scientific databases such as PubMed database of the National Library of Medicine, Scopus and Google Scholar without any time limitation. The extract of cinnamon efficiently inhibits tau accumulations, Aβ aggregation and toxicity in vivo and in vitro models. Indeed, cinnamon possesses neuroprotective effects interfering multiple oxidative stress and pro-inflammatory pathways. Besides, cinnamon modulates endothelial functions and attenuates the vascular cell adhesion molecules. Cinnamon PPs may induce AD epigenetic modifications. Cinnamon and in particular, cinnamaldehyde seem to be effective and safe approaches for treatment and prevention of AD onset and/or progression. However, further molecular and translational research studies as well as prolonged clinical trials are required to establish the therapeutic safety and efficacy in different cinnamon spp.